Effectiveness Concentration of Betel Leaf Extract (Peperbetle L.) on the Growth of Fusarium sp. in Vitro - Jasmi,; Adres Yanti, Lola; Chairuddin,; Suri Marlinda, Eka; Muslimah, Yuliatul (International Journal of Psychosocial Rehabilitation, 2020)
Fusariumsp is a fungus that has an important influence on human life because it acts as a pathogen in plants and humans and produces toxins. Fusarium sp. causes the permeability of paramkin cells to increase, thereby losing osmotic efficiency and resulting in wilting. Betel leaf extract contains phenylpropanoid compounds and tannins. This compound is antimicrobial and antifungal, which is strong and can inhibit the growth of several types of fungi, such as Escherichia coli, Salmonella, and Fusarium sp. The study was conducted in December 2018 in the Plant Physiology Lab, Faculty of Agriculture, UTU Aceh Barat. Material used: distilled water, 96% alcohol, PDA media, betel plant, and Fusariumsp; tools used: petri dishes, Bunsen lamps, piset, measuring cups, spatulas, ovens, microscopes, autoclaves, blenders, and aluminum foil. This research uses a non-factorial, randomized design (RAL), which is the concentration factor of betel leaf extract (K) consisting of three levels, namely: K0: 0%, K1: 10%, K2: 20%, and K3: 30%. The results showed the percentage of Fusarium sp. the largest was found in the concentration of betel leaf extract (30%).